Mapping evapotranspiration with the remote sensing ET algorithms METRIC and SEBAL under advective and non-advective conditions: accuracy determination with weighing lysimeters - Mkhwanazi, Mcebisi M., author; Chávez, José L., author; Colorado State University, publisher (Colorado State University. Libraries, 2013)
The Surface Energy Balance Algorithm for Land (SEBAL) is one of several remote sensing-based crop evapotranspiration (ET) models. One advantage that SEBAL has is its minimal requirement for ground-based weather data. However, its downside is that in the presence of advection it may underestimate ET. This is due to the use of a fixed evaporative fraction (EF) for the entire day. The EF value is used to extrapolate instantaneous ET to daily ET values, based on the assumption that EF at the time of satellite overpass is the same (remains constant) as for the rest of the day, and therefore can be used to estimate daily ET. METRIC on the other hand, uses the reference ET fraction ETrF, which is a ratio of actual crop ET to alfalfa reference ET. A study was therefore carried out to compare these two models under advective and non-advective conditions. A total of 9 Landsat 7 ETM+ images (2010-2012) were processed using both models, and ET was estimated for two alfalfa fields near Rocky Ford in Eastern Colorado. Both fields were equipped with precision monolithic weighing lysimeters. The remote sensing estimated daily ET was compared with lysimeter-based ET measurements. Results showed that there were larger errors in SEBAL than in METRIC, with errors up to 45 % for the former and up to 25 % for the latter. The largest errors occurred on windy and hot days when there was advection.
Hydrology days 2013
AGU hydrology days 2013
2013 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2013.